A New Method to Determine Antioxidant Activities of Biofilms Using a pH Indicator (Resazurin) Model System - Young-Teck Kim; Robert Kimmel; Xiyu Wang (Molecules, 2023)
Biopolymeric films were prepared with gelatin, plasticizer, and three different types of antioxidants (ascorbic acid, phytic acid, and BHA) corresponding to different mechanisms in activity. The antioxidant activity of films was monitored for 14 storage days upon color changes using a pH indicator (resazurin). The instant antioxidant activity of films was measured by a DPPH free radical test. The system using resazurin was composed of an agar, an emulsifier, and soybean oil to simulate a highly oxidative oil-based food system (AES-R). Gelatin-based films (GBF) containing phytic acid showed higher tensile strength and energy to break than all other samples due to the increased intermolecular interactions between phytic acid and gelatin molecules. The oxygen barrier properties of GBF films containing ascorbic acid and phytic acid increased due to the increased polarity, while GBF films containing BHA showed increased oxygen permeability compared to the control. According to “a-value” (redness) of the AES-R system tested with films, films incorporating BHA showed the most retardation of lipid oxidation in the system. This retardation corresponds to 59.8% antioxidation activity at 14 days, compared with the control. Phytic acid-based films did not show antioxidant activity, whereas ascorbic acid-based GBFs accelerated the oxidation process due to its prooxidant activity. The comparison between the DPPH free radical test and the control showed that the ascorbic acid and BHA-based GBFs showed highly effective free radical scavenging behavior (71.7% and 41.7%, respectively). This novel method using a pH indicator system can potentially determine the antioxidation activity of biopolymer films and film-based samples in a food system.